Treatment of diarrhea and dysentery through ethnomedicinal plants in the Jaunpur region of Garhwal Himalaya, India - Lal, Tarseem; Dangwal, Lakhi Ram; Rawat, Minakshi (Ethnobotany Research and Applications, 2024)
Background: Diarrhea and dysentery are leading causes of death and illness in rural areas of developing countries in worldwide and neighboring countries. Diarrhea ranking as the third most common cause of child mortality in India. It contributes to 13% of deaths in children under five years annually. Even at the present time, majority of the rural people of the country still rely on regional plants resources to treat many diseases, including diarrhea and dysentery. The aim of the present study was to document and record the utilization of ethnomedicinal plants and various herbal remedies for the management of gastrointestinal ailments, with a specific focus on combating diarrhea and dysentery in the rural area of Garhwal Himalaya, specifically the Jaunpur region in the study site. Methods: Ethnobotanical investigation was carried out in 12 villages (namely Dhanaulti, Rautu ki Beli, Nainbagh, Kempty, Thatyur, Almas, Kyari, Pantwari, Devalsari, Teva, Naag Tibba, and Ontal) with traditional practices, interviewing 138 local informants (90 males and 48 females). The various methods (group discussions, meetings, and questionnaires) to gather ethnomedicinal knowledge for curing diarrhea and dysentery treatment. Furthermore, in this study, the informant's consensus factor (ICF), use value (UV), and fidelity index (FI%) were also discussed for each of the studied species. Results: In this study, local informants utilized a total of 30 ethnomedicinal plant species (from 28 genera and 30 families) to treat diarrhea and dysentery. The percentage of plant species used for specific ailments was: diarrhea (32% spp.), dysentery (20%), digestive problems (14%), stomach problems (12%), gastroenteritis (8%), appetizers (6%), dyspepsia (4%), oral ulcers (2%), and flatulence (2%). The residents use specific plant parts for ethnomedicinal purposes, with the following distribution: bark (3% spp.), fruits (10%), flowers (3%), leaves (45%), rhizomes (7%), roots (13%), seeds (3%), stems (7%), twigs (3%), and whole plant (6%). The herbal preparations in use include decoction (56% spp.), infusion (20%), juice (12%), paste (8%), and powder (4%). Conclusion: The present communication provides valuable insights into the indigenous utilization and availability of ethnomedicinal plants for treating diarrhea and dysentery. It underscores the importance of documenting and preserving this rich reservoir of knowledge passed down through generations for future research endeavors. Keywords: Rural people, Child mortality, Gastrointestinal ailments, Herbal preparations, Tehri Garhwal